The competences in the digital era in the tourism and hospitality sector - Neves, Cátia (2021)
Currently, due to the Fourth Industrial Revolution, the world has been witnessing several changes at the technological level, which have been reflected in the way a society should operate, namely those organizations in the Tourism and Hospitality sector. Thus, these organizations are facing challenges, both in terms oftheir professionals’ skills and in terms of the products and services offered. The main objective of this study is to characterize the changes in the level of skills needed by professionals in the Tourism and Hospitality sector, while bearing in mind their perception of the new challenges brought by the actual Industrial Revolution. More specifically, to characterize the strategies used, and technical and relational challenges that organizations face in this new Era. In this study, the qualitative methodology was assumed, through the realization of semi-structured interviews, to twelve hospitality professionals in the north of Portugal. The interviews were transcribed verbatim and analysed according to Grounded Theory principles. The results of the study indicate that this Digital Era has brought changes to the skills needed by professionals in this sector. In addition to the necessary technical skills to perform each function, personal and interpersonal skills are becoming increasingly important. These skills, compared to technology, add more value, which in turn allows the hotel establishments to differentiate from one another. These findings are really relevant for both professionals in this sector and professionals in education systems. For the former, they can support the management of the business, as well as define the way the organizations operate. Concerning the educational professionals, they can adapt to the needs the sector has, regarding the skills that should be learned and developed throughout the students' academic path.